Effects of Ar and O2 Plasma Etching on Parylene C: Topography versus Surface Chemistry and the Impact on Cell Viability. Issue 3 (17th August 2015) - Kontziampasis, Dimitrios; Trantidou, Tatiana; Regoutz, Anna; Humphrey, Eleanor J.; Carta, Daniela; Terracciano, Cesare M.; Prodromakis, Themistoklis
Abstract : The effect of O2 and Ar plasma etching on poly(chloro‐p‐xylylene) (Parylene C) is thoroughly studied by atomic force microscopy, X‐ray photoelectron spectroscopy, and static contact angle measurements. Results indicate that O2 plasma changes the topography more drastically than Ar plasma. Furthermore, despite the fact that Ar plasma is expected to be chemically inert, both plasmas introduce O2 to the surface of the Parylene C films, while Ar plasma additionally reduces the amount of Cl present in the polymer. The effect on the viability of cultured cardiomyocytes is also examined, indicating that cells attach and survive both on Ar and O2 treated films in contrast to untreated Parylene. These observations can provide useful insight into the field of material science and tissue engineering. Abstract : The effects of O2 and Ar plasma on the nanotopography and surface chemistry of Parylene C are studied. Atomic force microscopy and X‐ray photoelectron spectroscopy indicate that O2 plasma changes the topography more drastically than Ar plasma. Both plasmas introduce O2 to Parylene, but Ar plasma reduces the amount of Cl. These observations are reflected on the viability of cultured cardiomyocytes.